Detection of cryptic taxa in Leptobrachium nigrops (Amphibia, Anura, Megophryidae), with description of two new species - Hamidy, Amir; Matsui, Masafumi; Nishikawa, Kanto; Belabut, Daicus M. (Zootaxa, 2012)
We evaluated taxonomic relationships among allopatric populations of Leptobrachium nigrops Berry & Hendrickson fromMalay Peninsula, Singapore, Indonesia (Belitung), and Borneo (Sarawak). Phylogenetic relationships estimated from thesequence data of mitochondrial 12S RNA, tRNAval , and 16S rRNA genes, and nuclear NCX1 and SLC8A genes revealedpresence of three distinct clades within L. nigrops: (1) true L. nigrops clade from Singapore and Malay Peninsula, (2) cladefrom Belitung, Indonesia and coastal area of Sarawak, Borneo, and (3) clade from Kanowit, Sarawak, an inland area ofBorneo. Each of these three genetic clades is considered to represent distinct species because they are genetically highlydivergent and morphologically distinguishable. We therefore describe the populations from Belitung and coastal area ofSarawak as L. ingeri sp. nov and the population from the inland area of Sarawak as L. kanowitense sp. nov. Ancestral L.kanowitense seems to have invaded Borneo Island much earlier than ancestral L. ingeri, whose dispersion occurred during the Pleistocene glacial periods.